Portrait photograph of an unidentified female child (Natick, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Henry Barrett (photographer):::Photographer:::::::::::: (United States; Natick, MA; Henry Barrett, 2023)
Portrait photograph of an unidentified female child (undated) by Henry Barrett, Natick, MA, from the personal collection of Alexander Wheelock Thayer.